POLYNOMIAL SOLUTIONS OF ALGEBRAIC ODRINARY DIFFERENTIAL EQUATIONS. II - Gorbuzov, V. N. (Matematichki Bilten, 1994)
Bordered method of definition of degrees of polynomial solutions of algebraic differential equations and entire solutions of irreducible Painleve's equations are considered. The coefficients of highest term of polynomial solutions and the quantity of polynomial solutions of different degrees of algebraic differential equations are found.